Biosynthetic access to the rare antiarose sugar via an unusual reductase-epimerase. Issue 15 (2nd April 2020) - Yan, Yijun; Yang, Jing; Wang, Li; Xu, Dongdong; Yu, Zhiyin; Guo, Xiaowei; Horsman, Geoff P.; Lin, Shuangjun; Tao, Meifeng; Huang, Sheng-Xiong
Abstract : Rubrolones, isarubrolones, and rubterolones are recently isolated glycosylated tropolonids with notable biological activity. Abstract : Rubrolones, isatropolones, and rubterolones are recently isolated glycosylated tropolonids with notable biological activity. They share similar aglycone skeletons but differ in their sugar moieties, and rubterolones in particular have a rare deoxysugar antiarose of unknown biosynthetic provenance. During our previously reported biosynthetic elucidation of the tropolone ring and pyridine moiety, gene inactivation experiments revealed that RubS3 is involved in sugar moiety biosynthesis. Here we report the in vitro characterization of RubS3 as a bifunctional reductase/epimerase catalyzing the formation of TDP-d -antiarose by epimerization at C3 and reduction at C4 of the key intermediate TDP-4-keto-6-deoxy-d -glucose. These new findings not only explain the biosynthetic pathway of deoxysugars in rubrolone-like natural products, but also introduce RubS3 as a new family of reductase/epimerase enzymes with potential to supply the rare antiarose unit for expanding the chemical space of glycosylated natural products.